2023
DOI: 10.3390/medicina59061071
|View full text |Cite
|
Sign up to set email alerts
|

The Switch from Ferric Gluconate to Ferric Carboxymaltose in Hemodialysis Patients Acts on Iron Metabolism, Erythropoietin, and Costs: A Retrospective Analysis

Abstract: Background and Objectives: Iron deficiency and anemia characterize patients on chronic hemodialysis (HD). Available intravenous iron agents, such as ferric gluconate (FG) and ferric carboxymaltose (FCM), vary in dosing regimens and safety profiles. The aim of the present study was to analyze the modification of the iron status, the correction of anemia, and the economic implications after the shift from FG to FCM therapy in chronic HD patients. We evaluated, during the study, the variations in iron metabolism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In addition, intravenous formulations of high-titer iron are now available on the market, allowing large amounts of iron to be administered intravenously in a single dose. Ferric carboxymaltose and ferric derisomaltose, which can be administered intravenously in large doses at once resulting in a reduction in oxidative stress, has been reported to improve anemia, reduce ESA, and increase ferritin and TSAT [34][35][36][37][38][39][40]. However, it has been suggested that highdose iron administration and a high ferritin level are associated with iron deposition in the liver [41,42] and iron deposition in the liver and heart has also been reported to be observed in many hemodialysis patients [43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intravenous formulations of high-titer iron are now available on the market, allowing large amounts of iron to be administered intravenously in a single dose. Ferric carboxymaltose and ferric derisomaltose, which can be administered intravenously in large doses at once resulting in a reduction in oxidative stress, has been reported to improve anemia, reduce ESA, and increase ferritin and TSAT [34][35][36][37][38][39][40]. However, it has been suggested that highdose iron administration and a high ferritin level are associated with iron deposition in the liver [41,42] and iron deposition in the liver and heart has also been reported to be observed in many hemodialysis patients [43].…”
Section: Discussionmentioning
confidence: 99%